PENDAMPINGAN LANSIA DI PANTI JOMPO ADINDA MULIA BAHAGIA - Liswandi; Pandu Adi Cakranegara (JURNAL ABDIMAS PLJ, 2024)
Many nursing home residents are individuals who have been abandoned by their families for various reasons, including financial difficulties, Family problems, or, worst of all, the ignorance of family members to give caregiving responsibilities. Consequently, these families often transfer the care of their elderly relatives to institutions like the Adinda Mulia Bahagia Foundation Nursing Homes, where residents may spend their remaining years without regular family visits or support. This abandonment significantly contributes to the emotional burden and trauma experienced by nursing home residents, many of whom are aware of their family abandoning them. As a result, nursing homes are often perceived as depressing place where elderly live the rest of their lives without their family connections that typically provide emotional support and family bond. This perception underscores the profound emotional and psychological challenges faced by these residents. In response to these challenges, our project aims to dedicate a day to engage and socialize with the nursing home residents with Citizenship, Pancasila, Religion knowledge. Through a variety of activities, we seek to relieve their emotional and mental burdens, providing moments of warm feelings and support, even if it is only for a day.